Antinormal Weighted Composition Operators. (10th October 2016) - Kumar, Dilip; Chandra, Harish
Abstract : Letl 2 = L 2 N, μ, whereN is set of all positive integers andμ is the counting measure whoseσ -algebra is the power set ofN . In this paper, we obtain necessary and sufficient conditions for a weighted composition operator to be antinormal on the Hilbert spacel 2 . We also determine a class of antinormal weighted composition operators on Hardy spaceH 2 D .